Optimalisasi Produk “Jus Lia” Desa Tepisari Kabupaten Sukoharjo melalui Pelatihan Digital Marketing - Al Ayyubi, Muhammad Faiz; Kusumawardani, Anggraini Putri; Mundy, Ken Cita (Ideas Publishing, 2024)
Tepisari Village, Sukoharjo Regency has local potential in the form of abundant aloe vera plants that can be used as a source of community economy. However, this potential has not been able to be maximized by the community. This research aims to examine how digital marketing training can increase the economic value of aloe vera through products in the form of